The New Testament of Our Lord and Savior Jesus Christ- The Book of Psalms (Philadelphia National Bible Press, 1942)
Translated out Of the Origional Tongues and With the Former Translations Diligently Compared and Revised
Made Especially for The Gideons
Conformable to The Edition of 1611 Commonly Known as The Authorized or King James Version
Keywords: Holy Bible Texts and Translations (3fUhU hJQLeGJ GdcJGH GdebOSs; Bible